(untitled) (American Journal of Islam and Society, 2002)
ls history progressive? Does progress lead to civilization? If history is progressive and progress leads to civilization, why then do civilizations rise and fall in history? These questions lead to more questions. What is progress? High rise buildings? fncrease in economic and material production? ’Increase in longevity? Does progress lead to easing life? ff it leads to easing life, does it bring happiness in human lives? Is there a crisis of civilization in our times? If there is, is there a remedy for this crisis? These questions have been raised and discussed extensively by historians and philosophers of history, and yet the debate has not ended. Jn fact as the twentieth century approached its end, the debate seemed to have become more and more live and controversial. Let us browse through the last two decades of this controversy.